Kozier & Erb's fundamentals of nursing : concepts, process, and practice / Audrey Berman, Shirlee J. Snyder, Geralyn Frandsen - Berman, Audrey
Kozier & Erb's Fundamentals of Nursing, Eleventh Edition, addresses the concepts of contemporary professional nursing. These concepts include but are not limited to caring, wellness, health promotion, disease prevention, holistic care, critical thinking and clinical reasoning, multiculturalism, nursing theories, nursing informatics, nursing research, ethics, and advocacy. In this edition, every chapter has been reviewed and revised. The content has been updated to reflect the latest nursing evidence and the increasing emphasis on aging, wellness, safety, and home- and community-based care